2011
DOI: 10.1007/s10147-011-0234-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of lymph node dissection in the management of urothelial carcinoma of the upper urinary tract

Abstract: Urothelial carcinoma of the upper urinary tract (UCUUT) is a disease with poor prognosis and a high incidence of lymphatic metastasis at 30-40%. Lymphadenectomy may be a possible surgical strategy to control the spread of lymphatic cancer, but its therapeutic benefit in UCUUT has remained controversial in contrast to bladder cancer in which consensus has been almost reached with respect to the necessity of extended lymphadenectomy. We hypothesized that radical lymphadenectomy may also be important for UCUUT si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…The impact of a LN dissection on UTUC‐related mortality is currently unknown. Patients with ≥pT2 stage seem to benefit most from a LN dissection . In our present study, LN density was an independent prognostic factor, but it did not impact the effect of AC.…”
Section: Discussioncontrasting
confidence: 55%
“…The impact of a LN dissection on UTUC‐related mortality is currently unknown. Patients with ≥pT2 stage seem to benefit most from a LN dissection . In our present study, LN density was an independent prognostic factor, but it did not impact the effect of AC.…”
Section: Discussioncontrasting
confidence: 55%
“…Based on the cumulative data from the literature, it seems that lymphadenectomy could offer a more accurate staging and also may remove (micro-)metastasis thereby resulting into improved outcomes[20, 24]. However, we did not control for the lymph node count nor for the anatomical template of lymphadenectomy, both of which might have influenced our results[20, 27]. Only a prospective study with standardized criteria and a clearly defined template may shed more light on the value of lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a Japanese group found that more complete LnD was associated with survival benefits compared to incomplete or no LnD (24). Moreover, retrospective data suggests that LnD may have more significant staging and therapeutic impact on outcome in patients with locally advanced disease compared to those with localized UTUC (16,24,25). However, even at the high volume academic centers included in this collaboration, LnD was performed only in 40-50% of cases (25).…”
Section: Discussionmentioning
confidence: 92%
“…Brausi et al demonstrated that LnD performed at the time of RnU significantly improved the survival of patients with invasive UTUC (23). Similarly, a Japanese group found that more complete LnD was associated with survival benefits compared to incomplete or no LnD (24). Moreover, retrospective data suggests that LnD may have more significant staging and therapeutic impact on outcome in patients with locally advanced disease compared to those with localized UTUC (16,24,25).…”
Section: Discussionmentioning
confidence: 99%